Effects of Brash Removal After Clear Felling on Soil and Soil-Solution Chemistry and Field-Layer Biomass in an Experimental Nitrogen Gradient - E. Ring; L. Hogbom; H.A. Nohrstedt (The Scientific World Journal)
Biofuels, such as brash from forest fellings, have been proposed as an alternative energy source. Brash removal may affect the sustainability of forest production, e.g., through a change in the availability of cations and N in the soil. We report initial effects of brash removal on inorganic N content in humus and mineral soil, soil-solution chemistry, and field-layer biomass after clear felling an N-fertilisation experiment in central Sweden. The experiment comprised six different fertiliser levels, ranging from 0 to 600 kg N ha1. Urea was given every 5th year during 1967 to 1982 to replicated plots, giving total doses of 0 to 2400 kg N ha1. Clear felling took place in 1995, 13 years after the last fertilisation. The removal of brash decreased the NO3 content in the humus layer after clear felling. A decrease in the NO3 concentration of the soil solution was indicated during most of the study period as well. No effect of the previous N fertilisation was found in the humus layer, but in the mineral soil there was an increase in NO3 content for the highest N dose after clear felling (p = 0.06). The soil-solution chemistry and the field-layer biomass showed an irregular pattern with no consistent effects of brash removal or previous fertilisation.